FACTORS INFLUENCE EMPLOYEE PERFORMANCE: A LITERATURE REVIEW - Mardika, Nanda Harry; Widia, Elli (Management Studies and Business journal, 2026)
Achieving organizational objectives is largely dependent on employee performance. The degree to which an employee can carry out his tasks and obligations correctly and successfully is measured by his performance. A thorough review of the elements influencing employee performance was used in this study. A literature review is a type of research study that aims to address a specific research issue by methodically locating, choosing, and assessing all pertinent material. sixteen papers that satisfied the predefined criteria were discovered by the researchers after the screening process. Research on the variables influencing employee performance focuses on a number of topics, including trade associations, incentives, management systems, KPIs, perceived overqualification, chefs, continuous improvement, system dynamics models, performance management implementation, compensation, benefits, and job satisfaction. Based on some of the findings of the study that has been conducted, we may draw the conclusion that employee performance is crucial since it is crucial to accomplishing organizational objectives. Therefore, in order to improve productivity, efficiency, and the caliber of work done, businesses must give staff performance management first priority.